2022
DOI: 10.5694/mja2.51651
|View full text |Cite
|
Sign up to set email alerts
|

More than a fleeting conversation: managing medication communication across transitions of care

Abstract: More than a fleeting conversation: managing medication communication across transitions of care Tailored medication communication is key to preventing patient harm across transitions of care O lder patients are likely to have complex medication regimens, which need to be carefully managed as they move across and within diverse settings, including primary care, acute care, geriatric rehabilitation, and aged care facilities. These movements often involve different health professionals, such as general practition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Previous research suggests that conversations with patients with complex medications tended to be brisk, one-way and controlled by healthcare professionals. 27 This can be due to traditional cultures of healthcare professionals leading care. 28 Researchers suggest that another reason that pharmacist interactions tended to be rushed was due to the high flow of patients being discharged, and doctors and nurses had limited discharge medication communication with patients due to time constraints and multitasking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research suggests that conversations with patients with complex medications tended to be brisk, one-way and controlled by healthcare professionals. 27 This can be due to traditional cultures of healthcare professionals leading care. 28 Researchers suggest that another reason that pharmacist interactions tended to be rushed was due to the high flow of patients being discharged, and doctors and nurses had limited discharge medication communication with patients due to time constraints and multitasking.…”
Section: Discussionmentioning
confidence: 99%
“…We found healthcare professionals were taking the initiative to start topics when patients were at high risk of medication-related problems; however, these conversations were largely monologues. Previous research suggests that conversations with patients with complex medications tended to be brisk, one-way and controlled by healthcare professionals 27. This can be due to traditional cultures of healthcare professionals leading care 28.…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy can be defned as individuals having the necessary skills, knowledge and motivation to access, and understand and apply health information when making decisions about their (or their family member's) care [45]. In addition, discussions among health care professionals, residents, and family members about medications, particularly during transitions of care, e.g., admission to an RACF, are an important mechanism to support residents and family members in having the necessary information to make informed medication management decisions [46].…”
Section: Discussionmentioning
confidence: 99%
“…Fragmentation in health care is frustrating for consumers and providers (CHFA 2022;Joo 2023). It increases pressure on the system due to unnecessary repetition of tests, duplication of care and greater potential for communication errors (Manias et al 2017(Manias et al , 2022. Duckett (2015) has suggested that 'making existing health services work well together would be the greatest step to sustainability' without a reduction in output or services.…”
Section: Challengesmentioning
confidence: 99%